The effects of climate change on the virtual water of some crops in Kerman province - Mohammadsaleh Ekhlasi; Somayeh Soltani-Gerdefaramarzi; Abolfazl Azizian; Morteza Gheysouri (تحقیقات کاربردی علوم جغرافیایی)
In this study, we examined the impact of climate change on the virtual water content of key crops in Kerman province for future periods. Specifically, we utilized the climatic data from the HadCM3 model under the RCP4.5 radiative forcing scenario. The model was calibrated and validated for the base period of 1991-2011. We predicted the precipitation levels, as well as the maximum and minimum temperatures, for selected stations from 2011 to 2070 using data from LARS-WG. These predictions were then compared to the base period. The virtual water content was calculated for three selected crops: alfalfa, barley, and wheat. Our findings indicate that climate change has a significant impact on evapotranspiration and the performance of these crops, consequently affecting future agricultural water productivity. As we project an increase in average temperature during the growing season due to climate change, it is worth noting that the maximum temperature parameter will be more affected by this phenomenon than the minimum temperature. This, in turn, will lead to increased water requirements and plant evaporation-transpiration during this period. Our research also reveals a decrease in precipitation during hot seasons and an increase during cold seasons across all study stations. Notably, the virtual water content for all crops studied demonstrates an upward trend, with barley and wheat showing the greatest average increase in the future period. Specifically, the Kerman station exhibits a substantial increase in virtual water content for barley and alfalfa products, at a minimum of 30% higher than the base period.